Factors Affecting Minimizing Excess of Budget Calculation Village Fund - Dariana, Dariana; Huri, Defri Daman; Hendarsyah, Decky; Susilawati, Susilawati (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study analyses the influence of village apparatus competence, internal control system and village fund accountability on minimizing the excess of budget calculation village fund. This study uses a descriptive quantitative approach based on primary and secondary data. Data collection techniques use questionnaires and literature. The population of this study was all village apparatuses of Bantan Tengah, Bengkalis sub-district, Bengkalis regency, Riau, totaling 27 people. The sampling technique uses saturated samples so that the number of samples is the same as the population. The data analysis technique uses multiple linear regressions with statistical tools like SPSS software. The study results show that village apparatus competence, internal control system, and village fund accountability positively and significantly affect minimizing the excess of budget calculation village fund. The results of this study can complement existing theories, provide novelty in excess of budget calculation village funds, and add new insights to the perspective of village fund management. Then, the results of this study can be a reference for the village government in minimizing the excess of budget calculation in village fund management.